Rational exemption to vaccination for non-fatal SIS diseases: Globally stable and oscillatory endemicity - Bruno Buonomo; Alberto d’Onofrio; Deborah Lacitignola (Mathematical Biosciences and Engineering)
'Rational' exemption to vaccination is due to a pseudo-rational comparison betweenthe low risk of infection, and the perceived risk of side effects fromthe vaccine. Here we consider rational exemption in an SI model withinformation dependent vaccination where individuals use information on thedisease's spread as their information set. Using suitable assumptions, we show the dynamic implications of theinteraction between rational exemption, current and delayed information. In particular, if vaccination decisions are basedon delayed informations, we illustrate both global attractivity to an endemic state, and the onset, through Hopf bifurcations, of general Yakubovich oscillations. Moreover, in some relevant cases, we plot the Hopf bifurcation curves and we give a behavioural interpretation of their meaning.